Film American Beginnings of Philippine Cinema - Deocampo, Nick ([Center for Cinema], 2012)
The second episode in Nick Deocampo's continuing saga on the history of Philippine cinema, this documentary recreates through 3D-rendered animation the evolution of motion pictures during the period of U.S. colonization of the Philippines. Introduced during the time of the Philippine-American War, American film pioneers under the protection of the U.S. military made the first cinematic representations of the country and its people. With Hollywood on the rise in the decades that followed, American influences shaped the growth of cinema in the Pacific colony through technology, language (both oral and visual), mode of production, aesthetics, and ideology. Before cinema became the 'national' culture that it would later assume, this documentary unravels Philippine cinema's colonial past that laid down the foundations of today's Filipino cinema. This documentary is based on Deocampo's book, Film: American Influences on Philippine Cinema.